2023
DOI: 10.3390/ijerph20126162
|View full text |Cite
|
Sign up to set email alerts
|

“They Tarred Me with the Same Brush”: Navigating Stigma in the Context of Child Removal

Abstract: Child removals are increasing in England and Wales. Family court involvement is particularly common among women with multiple disadvantages, and the rates are higher in economically marginalised areas. This article aims to explore women’s narratives of child removal within life stories of homelessness and examines how stigma, power and State surveillance manifest in their experiences. Data drawn from qualitative interviews with 14 mothers in the north-east of England who had experienced the removal of their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…when they're trying to get the kids off ya, they will tell whatever lies in front of the judge, in legal documents and it's basically your word against theirs and they're the professional so.' (FG3P3) Women explained that child removal was incredibly traumatic and often resulted in increased substance usage to cope with the grief, which concurs with existing findings [13,14]. Women felt they had failed their children, which induced shame.…”
Section: Discriminatory Practice Language Mistakes and Misconductmentioning
confidence: 61%
See 3 more Smart Citations
“…when they're trying to get the kids off ya, they will tell whatever lies in front of the judge, in legal documents and it's basically your word against theirs and they're the professional so.' (FG3P3) Women explained that child removal was incredibly traumatic and often resulted in increased substance usage to cope with the grief, which concurs with existing findings [13,14]. Women felt they had failed their children, which induced shame.…”
Section: Discriminatory Practice Language Mistakes and Misconductmentioning
confidence: 61%
“…Some drug strategy approaches [1] contravene international research findings, including tougher sentences for recreational users [11]. Punitive approaches can deter people from treatment; for example, state child removal fear is a barrier to women seeking help for alcohol use [12], and child removal can trigger increased substance usage [13,14]. Structural issues can exacerbate substance usage [15,16], and Link and Phelan [17] identify a power requirement to stigmatise others, for example, social, economic, and political power.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research team found that the stigma associated with child removal further entrenched social exclusion and increasing health inequalities. You can read more about the findings in the two articles published from the study (McGrath et al, 2023a(McGrath et al, , 2023b.…”
mentioning
confidence: 99%